2018
DOI: 10.19173/irrodl.v19i2.3443
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assurance for Online Higher Education Programmes: Design and Validation of an Integrative Assessment Model Applicable to Spanish Universities

Abstract: The quality assurance of online Higher Education online programmes is one of the great challenges faced by Spanish universities. Regular assessment of these programmes is essential in order to take actions to improve their quality. The said assessment should be complex and include all of the components of the programme, as well as its planning and implementation stages and its effects. The purpose of this paper is to present a model designed to assess the quality of online Higher Education online programmes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 10 publications
0
15
0
6
Order By: Relevance
“…Effort on QA in online learning has been strengthened through publication of guidelines (Uvalić-Trumbić and Daniel, 2013; Grifoll et al , 2010; Huertas et al , 2018). Research on QA for online higher education programs has been conducted identifying the system of indicators for the quality assessment for online higher education programs (Marciniak, 2018) and using PDPP (planning, development, process and product) evaluation model (Zhang and Cheng, 2012). Effective implementation of QA system in OUs, ODL and online learning system has been daunting tasks and shared responsibilities by the management, people, and stakeholders involved in ODL(Alfonso, 2015; Belawati and Zuhairi, 2007; Bibi et al , 2018; Jamandre, 2011; Jung et al , 2013).…”
Section: Meaning Of Qualitymentioning
confidence: 99%
“…Effort on QA in online learning has been strengthened through publication of guidelines (Uvalić-Trumbić and Daniel, 2013; Grifoll et al , 2010; Huertas et al , 2018). Research on QA for online higher education programs has been conducted identifying the system of indicators for the quality assessment for online higher education programs (Marciniak, 2018) and using PDPP (planning, development, process and product) evaluation model (Zhang and Cheng, 2012). Effective implementation of QA system in OUs, ODL and online learning system has been daunting tasks and shared responsibilities by the management, people, and stakeholders involved in ODL(Alfonso, 2015; Belawati and Zuhairi, 2007; Bibi et al , 2018; Jamandre, 2011; Jung et al , 2013).…”
Section: Meaning Of Qualitymentioning
confidence: 99%
“…Higher education institutions could use external QA processes to sustain their development [42]; however, these processes have to be carefully designed to conform to the missions of the institutions. Leadership that is committed to ensuring a safe and creative college environment is essential for designing effective QA processes [43]. Indeed, studies in higher education in Nigeria have shown that for the attainment of quality higher education, any QA system must include physical facilities and infrastructure, innovations, quality teaching, human resources, and curriculum innovation that conform to market demand [44].…”
Section: Quality Assurancementioning
confidence: 99%
“…Monitoring and ensuring the quality of online education is one of the key components of ensuring the sustainability of online university education. This issue is crucial for Ukrainian universities and is quite thoroughly developed in modern education science (Huertas, 2018;Marciniak, 2018). In current research on the quality of online university education, scientists (Huertas, 2018) identify ten main components that should be taken into account by universities (Huertas, 2018: 6/16): 1) Policy for quality assurance; 2) Design and approval of programs;…”
Section: Quality Assurancementioning
confidence: 99%